Squamous Cell Carcinoma Development Secondary to Chronic Osteomyelitis: A Case Report - Ezırmık, Naci; Yıldız, Kadri (Fırat University, 2012)
Squmaous cell carcinoma is a very rare clinical condition encountered as a complication of chronic osteomyelitis. Chronic osteomyelitis is a serious complication of fractures or crush injuries that has to be treated appropriately. Similarly, squamous cell carcinoma is considered as the last complication that has been considered by most of the orthopaedists. In this case report, it was aimed to highlight the importance of correct diagnosis and treatment of both chronic osteomyelitis an done of its complication squamous cell carcinoma.

Skuamöz hücreli karsinom kronik osteomiyelitin komplikasyonlarının çok nadir bir klinik halidir. Kronik osteomiyelit is kırıkların ve ezilme yaralanmalrının ciddi bir komlikasyonudur ve ciddi bir şekilde tedavi edilmelidir. Ayrıca ortopedistlerin aklında skuamöz hücreli karsinom genellikle en son komplikasyondur. Bu vaka sunumunda kronik osteomiyelitin ve onun bir komplikasyonu olan skuamöz hücreli karsinomun doğru tanı ve tedavisinin önemini vurgulamak amaçlanmıştır.
Kronik Osteomiyelite Sekonder Gelişen Skuamöz Hücreli Karsinom: Olgu Sunumu